Pengaruh Pemahaman Terminologi Ekonomi Dan Bisnis Dalam Bahasa Arab Terhadap Karier Di Bidang Ekonomi Dan Bisnis - Nicky Putri Ramadhanti; Madian Muhammad Muchlis (STIKes Ibnu Sina Ajibarang, 2024)
Understanding the terminology of economics and business in the Arabic language is important for careers in the field of economics and business. This is because Arabic is an important language in the Islamic world, including in the field of economics and business. This study aims to analyze the influence of understanding the terminology of economics and business in the Arabic language on careers in the field of economics and business. This study uses a qualitative method with a literature review approach. Research data was collected by searching for articles relevant to the research topic. The results of the study show that understanding the terminology of economics and business in the Arabic language has a positive influence on careers in the field of economics and business. This can be seen from its influence on understanding economic and business literature, communication with colleagues, and job opportunities. This study concludes that understanding the terminology of economics and business in the Arabic language is important for careers in the field of economics and business. Therefore, it is important for someone who wants to pursue a career in this field to learn the terminology.